2017
DOI: 10.7717/peerj.3966
|View full text |Cite
|
Sign up to set email alerts
|

Species–specific crab predation on the hydrozoan clinging jellyfish Gonionemus sp. (Cnidaria, Hydrozoa), subsequent crab mortality, and possible ecological consequences

Abstract: Here we report a unique trophic interaction between the cryptogenic and sometimes highly toxic hydrozoan clinging jellyfish Gonionemus sp. and the spider crab Libinia dubia. We assessed species–specific predation on the Gonionemus medusae by crabs found in eelgrass meadows in Massachusetts, USA. The native spider crab species L. dubia consumed Gonionemus medusae, often enthusiastically, but the invasive green crab Carcinus maenus avoided consumption in all trials. One out of two blue crabs (Callinectes sapidus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 66 publications
0
9
0
Order By: Relevance
“…may mediate the interactions of other species and cause mortality in non-prey organisms. For example, along the Northwest Atlantic coast in Massachusetts, Carman, Grunden & Govindarajan (2017) found that Gonionemus sp. was consumed by a native spider crab but not by the invasive green crab.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…may mediate the interactions of other species and cause mortality in non-prey organisms. For example, along the Northwest Atlantic coast in Massachusetts, Carman, Grunden & Govindarajan (2017) found that Gonionemus sp. was consumed by a native spider crab but not by the invasive green crab.…”
Section: Discussionmentioning
confidence: 99%
“…These hydromedusae can have a potent sting that causes severe pain and other symptoms to humans (Pigulevsky & Michaleff, 1969; Otsuru et al, 1974; Yakovlev & Vaskovsky, 1993; Govindarajan & Carman, 2016; Marchessaux et al, 2017). As well, they can be lethal to their predators (Carman, Grunden & Govindarajan, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…may mediate the interactions of other species and cause mortality in non-prey organisms. For example, along the Northwest Atlantic coast in Massachusetts, Carman et al (2017) found that Gonionemus sp. was consumed by a native spider crab but not by the invasive green crab.…”
Section: Clinging Jellyfish Have Been Previously Reported From Europementioning
confidence: 99%
“…These hydromedusae can have a potent sting that causes severe pain and other symptoms to humans (Pigulevsky & Michaleff, 1969;Otsuru et al, 1974;Yakovlev & Vaskovsky, 1993;Govindarajan & Carman, 2016;Marchessaux et al, 2017). As well, they can be lethal to their predators (Carman et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, high densities of Gonionemus sp. may have a negative effect on the inhabitants of Martha's Vineyard eelgrass ecosystems as it is potentially lethal to predators (Carman et al 2017). Thus, it is important to understand its regional distribution, habitat constraints, and spread in this area.…”
Section: Introductionmentioning
confidence: 99%